2010
DOI: 10.1007/s11751-010-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone lengthening osteogenesis, a combination of intramembranous and endochondral ossification: an experimental study in sheep

Abstract: We evaluated the morphological features of the newly formed tissue in an experimental model of tibial callotasis lengthening on 24 lambs, aged from 2 to 3 months at the time of operation. A unilateral external fixator prototype Monotube Triax® (Stryker Howmedica Osteonics, New Jersey) was applied to the left tibia. A percutaneous osteotomy was performed in a minimally traumatic manner using a chisel. Lengthening was started 7 days after surgery and was continued to 30 mm. The 24 animals were randomly divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
(44 reference statements)
1
17
1
1
Order By: Relevance
“…Whereas in distraction gaps the tissue between the ends of the mineralised bone is first subject to bleeding, coagulation, granulation tissue and fibrosis (Kokich, 1976;Shapiro, 2008), bone directly develops at the suture edges in craniosynostosis. In addition, in contrast to the distraction gap (Yasui et al, 1997;Jazrawi et al, 1998;Sato et al, 1998;Ploder et al, 2002;Lafuente et al, 2009;Forriol et al, 2010), our analyses of sutural sites showed no verification of enchondral and transchondroid types of osteogenesis.…”
Section: J Regelsberger Et Alcontrasting
confidence: 79%
“…Whereas in distraction gaps the tissue between the ends of the mineralised bone is first subject to bleeding, coagulation, granulation tissue and fibrosis (Kokich, 1976;Shapiro, 2008), bone directly develops at the suture edges in craniosynostosis. In addition, in contrast to the distraction gap (Yasui et al, 1997;Jazrawi et al, 1998;Sato et al, 1998;Ploder et al, 2002;Lafuente et al, 2009;Forriol et al, 2010), our analyses of sutural sites showed no verification of enchondral and transchondroid types of osteogenesis.…”
Section: J Regelsberger Et Alcontrasting
confidence: 79%
“…However, during the consolidation phase, bone volume is created quickly in a disorganized way with the aim of recovering the force sustained by the limb. 20,24,25,44 The device (instrumented fixator and acquisition system; Fig. 2) used in this study or similar designs increase the future possibilities of assessing consolidation in combination with conventional methods (such as Xrays or ex vivo tests).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, both methods have been proven inexact. 35,36,50 In addition, as these traditional techniques, many of the existing studies 3,5,6,13,20,24,25,27,34 are not able to provide the sufficient quantitative information that sometimes may be necessary; e.g., to evaluate the time to remove the fixator. Therefore, new quantitative techniques for assessing callus volume and material properties are required to optimize clinical treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter pathway, although also present in fracture repair, is integral to bone defect repair, distraction osteogenesis and implant fixation. 9,25,26 Like nearly all wound repair responses, intramembranous bone formation following marrow ablation has inflammatory, repair and remodeling phases each of which are time-dependent, characterized histologically and genetically. 4 These phases for intramembranous bone formation are distinct from endochondral-based fracture repair.…”
Section: Introductionmentioning
confidence: 99%